Efficacy of Immune Checkpoint Inhibitors in Patients With EGFR Mutated NSCLC and Potential Risk Factors Associated With Prognosis: A Single Institution Experience - Bai, Menglin; Wang, Weiqing; Gao, Xuetian; Wu, Leilei; Jin, Peng; Wu, Hui; Yu, Jinming; Meng, Xue (Frontiers in Immunology, 2022)
Background The role of immune checkpoint inhibitors (ICIs) in NSCLC patients with EGFR mutations are controversial. In this study, we aim to investigate the therapeutic efficacy of ICIs alone or in combination in patients with EGFR mutated NSCLC in late-line settings, and explore the factors that may predict the efficacy of ICIs. Patients and Methods We retrospectively collected the clinical and pathological information of 75 patients with confirmed EGFR mutations. All patients have developed acquired resistance to EGFR-TKIs, and were treated with ICIs in late line settings from January 2019 to January 2021, at Shandong Caner Hospital and Institute. Therapeutic efficacy was evaluated by tumor response and survival. Results The median follow-up period was 7.3months (range 1.8-31.8 months). The overall response rate (ORR) was 8.0%, and the disease control rate (DCR) was 78.7%. The median PFS for all patients was 3.9 months (95% CI, 2.7-5.0), while the median OS was 9.9 months (95% CI, 5.3-14.6). We found that patients with longer response duration to EGFR-TKIs (≥10 months) showed a longer PFS when treated with immunotherapy compared with patients with shorter PFS-TKI (<10 months), the median PFS in two groups were 5.2 months [95%CI 4.2-6.2] and 2.8 months [2.0-3.6]) respectively (HR, 0.53, 95%CI, 0.31-0.91, P=0.005). In exploratory analysis, we found that concurrent extracranial radiotherapy and higher body mass index (BMI) are associated with longer PFS (P values are 0.006 and 0.021 respectively). Conclusions We found that combination regimen of immunotherapy plus chemotherapy plus antiangiogenetic agents may yield longer survival in patients with EGFR mutated NSCLC. We also found that patients with longer PFS-TKI, concurrent extracranial radiotherapy and higher BMI may benefit more from immunotherapy.